2019
DOI: 10.5007/1980-0037.2018v20n6p585
|View full text |Cite
|
Sign up to set email alerts
|

Motives for sports practice in young soccer and volleyball athletes

Abstract: The reasons why athletes, especially young people, seek to adhere to sports practice has aroused the interest of research. The aim of this study was to identify the reasons for the sports practice of young soccer and volleyball athletes according to gender, age, family economic class, practice time and level of competitiveness. 188 athletes, 56 volleyball athletes and 132 soccer players aged 10-16 participated in the study. The reasons for the sport were identified through the Participation Motivation Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
1
6
1
5
Order By: Relevance
“…When analyzing the results of the present study with pupil-athletes, it is notable that the reasons for the practice of sport in pupil-athletes, in general, are similar to some other studies, which also obtained results showing that the dimensions Competition and/or Technical Competence are the most important for the practice of sports [24][25][26]. This finding should not be seen as unusual, since it is totally understandable that this population has a preference for reasons that are associated with success in the sporting context.…”
Section: Girlssupporting
confidence: 85%
See 1 more Smart Citation
“…When analyzing the results of the present study with pupil-athletes, it is notable that the reasons for the practice of sport in pupil-athletes, in general, are similar to some other studies, which also obtained results showing that the dimensions Competition and/or Technical Competence are the most important for the practice of sports [24][25][26]. This finding should not be seen as unusual, since it is totally understandable that this population has a preference for reasons that are associated with success in the sporting context.…”
Section: Girlssupporting
confidence: 85%
“…In addition, it also disregards the result of the most important reasons for the practice of sports being related to the search for improvement and maintenance of technical skills. Some investigations [25] direct attention to the dimensions that were pointed out with a lesser value of importance in this study: Affiliation and Emotion. There are hypotheses that these dimensions associated with intrinsic motivation could be responsible for the decision to practice a sport modality [28].…”
Section: Girlsmentioning
confidence: 96%
“…In another study, gender motivations were compared in team sports versus individual sports, and it was found that female athletes had higher overall motivation to participate in sports than male athletes (Moradi et al, 2020). Another finding in the context of gender comparisons in team sports (i.e., football and volleyball) showed that girls and boys attached importance to the same three motives for participating ("technical ability", "competition" and "group activity") but differed in the level of importance of each factor (Vignadelli et al, 2018). This, added to findings showing a significant gap in drop-out numbers between the genders, increases the importance of investigating motivational patterns among female athletes to join sport activity, to persist in participation and finally to drop out.…”
Section: Introductionmentioning
confidence: 98%
“…According to research studies, significant components of individual intrinsic motivation include enjoyment of play and competition (Soares et al, 2013), im-Psychology proving abilities and performance, the ability to face challenges and competitions (Vignadelli et al, 2018), a sense of ability, a sense of comfort with oneself, and belonging and connection to a team (Zarrett et al, 2020). It was explained that these interpersonal factors are Influenced both by personal experiences in sports and by the opinions of other important people in their environment such as family and friends (Zarrett et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Os principais fatores motivacionais desta fase são o prazer, competência técnica, afiliação e condição física. Aderem à uma modalidade por perceber que é muito divertido estar ao lado de amigos, conhecer novas pessoas e que isso facilita atingir as desejadas competências e aptidões físicas (Vignadelli et al, 2018).…”
Section: Introductionunclassified